Phosphatidylcholine (lecithin) and the mucus layer: evidence of therapeutic efficacy in ulcerative colitis? - Stremmel, Wolfgang; Hanemann, Anja; Ehehalt, Robert; Karner, Max; Gauss, Annika (Digestive diseases, 2010)
Colonic mucus protects against attacks from bacteria in stool. One component of mucus is phosphatidylcholine (PC) which is thought to be arranged as continuous lamellar layer in the apical mucus and to be responsible for establishing a protective hydrophobic surface. This ‘intestinal surfactant’ plays a key role in mucosal defense. Thus, a defective PC layer contributes to the development of inflammation. Analysis of rectoscopically acquired mucus aliquots revealed a 70% decrease in PC content in ulcerative colitis (UC) compared to Crohn´s disease (CD) and healthy controls - independent of disease activity. Accordingly, we propose that lack of mucus PC is a key pathogenetic factor in UC. In clinical studies a delayed-release oral PC preparation (rPC) was found to substitute the lack of PC in rectal mucus. Indeed, in non-steroid-treated active UC, 53% of rPC patients reached remission [clinical activity index (CAI) ≤3] compared to 10% of placebo patients (p ≤ 0.001). Endoscopic and histologic findings improved concomitantly. A second trial with 60 chronic-active, steroid-dependent UC patients was conducted to test for steroid-sparing effects. Complete steroid withdrawal with a concomitant achievement of remission (CAI ≤3) or clinical response (≧50% CAI improvement) was reached in 15 PC-treated patients (50%) but only in 3 (10%) placebo patients (p = 0.002). In conclusion, intrinsic reduction of PC (lecithin) in colonic mucus may be a key pathogenetic feature of UC. Topical supplement of PC by a delayed-released oral PC preparation is effective in resolving inflammatory activity of UC and may develop to a first-choice therapy for this disease.
Gesehen am 01.09.2023